Description of the Sense of Community in Regional Leadership Members of the East Java Ikatan Pelajar Muhammadiyah : Gambaran Sense of Community pada Pengurus Pimpinan Wilayah Ikatan Pelajar Muhammadiyah Jawa Timur - Rahmawati, Axnes Tasya; Mariyati, Lely Ika (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the relationship between sense of community and performance among members of the Muhammadiyah Student Association in East Java. Employing a descriptive quantitative research method, data were collected from a population of 65 individuals using saturated sampling. Research instruments, derived from previous studies, demonstrated satisfactory validity and reliability. Results reveal a predominantly high sense of community among members, with 9.20% categorized as very high, 21.50% as high, 43.20% as medium, 20% as low, and 6.10% as very low. These findings underscore the importance of fostering a strong sense of community within groups, as it positively impacts individual and collective performance, thus offering valuable insights for community development and organizational management. Highlights: Importance of sense of community: Emphasizes the role of community cohesion in driving individual and collective performance. Research methodology: Descriptive quantitative approach provides an overview of sense of community among members. Findings: Majority of members exhibit high to very high sense of community, highlighting strong group cohesion within the Muhammadiyah Student Association in East Java. Keywords: Community, Sense of Community, Ikatan Pelajar Muhammadiyah